Financing Management as a Driver of Quality in Islamic Educational Institutions: A Case Study at MI Nurudzolam, Pare, Kediri - Ma’sum Thoyib; Fitdarus Kussuma (proceedings.icesy, 2026)
Purpose This study aims to analyze the role of effective financing management as a driver for improving the quality of Islamic educational institutions by examining the mechanisms of evaluation, internal oversight, and financial accountability at MI Nurudzolam, Pare, Kediri. Design /methodology/approach This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation studies, and then analyzed using the Miles and Huberman interactive model (data reduction, data display, conclusion drawing/verification). Findings: The results reveal three key findings: (1) regular evaluation of fund usage enhances financing effectiveness through precise budget adjustments; (2) internal oversight by the head of the madrasah fosters a culture of discipline and budget compliance; (3) periodic financial reporting strengthens institutional accountability and transparency. These findings indicate that financing management is not merely an administrative aspect but a strategic instrument directly driving improvements in learning quality, facilities, and educator competence. Originality/value: This research contributes to strengthening the concept of Islamic education financing management by offering an efficient, accountable, and quality-responsive fund management model. This model integrates modern governance principles with Islamic educational values, making it relevant for application in contemporary Islamic educational institutions.